2022
DOI: 10.3390/su142215385
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Faecal Sludge Biochar and Biosolids Use in Agriculture

Abstract: Full-scale pyrolysis of faecal sludge is a credible technology for the safe removal of pathogens and the concurrent creation of biochar, which has been shown to enhance crop productivity. Faecal sludge biochar has the potential to improve acidic, low nutrient soils and crop yield in developing nations more at risk of climate change and food insecurity. Little research has been conducted into public acceptance of faecal sludge biochar as a soil enhancer in agriculture. In this study of the public in Swansea, Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Despite this statement, respondents aged 26-60+ mostly declared knowledge on SS utilization in agriculture and land reclamation (28-56%), composting (10-16%), or landfilling (5-28%) (Table 4). A study by Nicholas et al [40] confirmed that the oldest age group of respondents (65+) had greater knowledge and acceptance of the agricultural use of sewage sludge compared to young ones. Mela et al [41] also found greater knowledge of wastewater management among older people (over 65 years of age) than young people.…”
Section: Public Awareness and Knowledge In The Local Community Regard...mentioning
confidence: 95%
“…Despite this statement, respondents aged 26-60+ mostly declared knowledge on SS utilization in agriculture and land reclamation (28-56%), composting (10-16%), or landfilling (5-28%) (Table 4). A study by Nicholas et al [40] confirmed that the oldest age group of respondents (65+) had greater knowledge and acceptance of the agricultural use of sewage sludge compared to young ones. Mela et al [41] also found greater knowledge of wastewater management among older people (over 65 years of age) than young people.…”
Section: Public Awareness and Knowledge In The Local Community Regard...mentioning
confidence: 95%
“…Also, age plays a significant part in perceptions of FS biochar with those in the oldest age group having the most positive attitude towards FS biochar. Therefore, in the future it is critical to consider gender differences, issue awareness, age and the "disgust factor" when implementing management and policy decisions regarding the land application of biosolids and FS biochar (H. L. Nicholas, Halfacree, et al, 2022).…”
Section: Public Perception Of Faecal Sludge Biocharmentioning
confidence: 99%